2004
DOI: 10.1152/ajpheart.00409.2004
|View full text |Cite
|
Sign up to set email alerts
|

FKBP12.6 overexpression decreases Ca2+ spark amplitude but enhances [Ca2+]i transient in rat cardiac myocytes

Abstract: Gómez, Ana M., Iris Schuster, Jérémy Fauconnier, Jü rgen Prestle, Gerd Hasenfuss, and Sylvain Richard. FKBP12.6 overexpression decreases Ca 2ϩ spark amplitude but enhances [Ca 2ϩ ]i transient in rat cardiac myocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 35 publications
(66 reference statements)
9
45
0
Order By: Relevance
“…This means that only ,35% of available sites are occupied in mouse RyR2, ,45% in pig and rat RyR2, and virtually zero in rabbit. This finding might explain the beneficial effects on SR Ca 2+ handling upon FKBP12.6 overexpression in isolated cardiomyocytes (Gomez et al, 2004;Loughrey et al, 2004;Prestle et al, 2001) or in transgenic animals (Gellen et al, 2008;Huang et al, 2006;Seidler et al, 2011). If RyR2 channels were already saturated by FKBP12.6, then overexpression of this protein should be ineffective in improving SR Ca 2+ handling, as previously suggested (Gellen et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This means that only ,35% of available sites are occupied in mouse RyR2, ,45% in pig and rat RyR2, and virtually zero in rabbit. This finding might explain the beneficial effects on SR Ca 2+ handling upon FKBP12.6 overexpression in isolated cardiomyocytes (Gomez et al, 2004;Loughrey et al, 2004;Prestle et al, 2001) or in transgenic animals (Gellen et al, 2008;Huang et al, 2006;Seidler et al, 2011). If RyR2 channels were already saturated by FKBP12.6, then overexpression of this protein should be ineffective in improving SR Ca 2+ handling, as previously suggested (Gellen et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
“…The finding that FKBP12.6 occupancy of RyR2 is low (or near absent in rabbit) suggests that this protein might not be vital for normal heart function. However, at full saturation FKBP12.6 has the potential to further stabilise RyR2 function and reduce diastolic SR Ca 2+ leak, as indicated by overexpression studies in isolated cardiomyocytes (Gomez et al, 2004;Loughrey et al, 2004;Prestle et al, 2001) and transgenic animals (Gellen et al, 2008;Huang et al, 2006;Seidler et al, 2011). Recent work has demonstrated that FKBP12.6 levels are increased in the late preconditioned myocardium and that this protects against myocardial stunning (Lucats et al, 2007).…”
Section: Implications For Ryr2 Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a 12.6-kDa protein that is thought to bind to each subunit of the channel in a 1:1 ratio on the cytosolic side of RyR (478,951). FKBP12.6 is considered a RyR channel stabilizer in the closed state during diastole, and it appears to faciltitate the functional coupling of RyR channels (534,981 (280,710). Unique to the rat myocyte was the finding that FKBP12.6 overexpression hastened Ca 2ϩ transient decay (280,710).…”
Section: Fkbp126/calstabin2mentioning
confidence: 99%
“…In a previous study, modulators of RyR1 open and closed states had no effect on the quantity of FKBP12 bound to RyR1 in GST-FKBP12 pulldown assays (Bultynck et al, 2001), thus our observations reflect the discriminatory power of the SPR technique. The impact of complete loss of FKBP12/12.6 from RyR1/RyR2 are changes in the stability of the open/closed state of RyR in bilayers (Ahern et al, 1997;Brillantes et al, 1994;Chen et al, 1994;Ma et al, 1995) and altered EC coupling and Ca 2+ sparks in skeletal (Avila et al, 2003) and cardiac (Gomez et al, 2004;Prestle et al, 2001;Xiao et al, 1997) myocytes. Our data suggests that, because FKBP12 dissociates slowly and retains a comparatively high affinity for the open channel, loss of FKBP12 from RyR may not be a part of the normal EC coupling cycle.…”
Section: Discussionmentioning
confidence: 99%